Decolorization of Disperse Orange 25 using Trichosanthes diocia proteins in the presence of redox mediator - Jamal, Farrukh (Recent Research in Science and Technology, 2010)
Abstract This paper describes a peroxidase from Trichosanthes diocia to study decolorization of Disperse Orange 25 under different experimental conditions like pH, temperature, time interval, enzyme concentration and in the presence of redox mediators 1-hydroxybenzotriazole (HOBT).T. diocia peroxidase showed remarkable decolorization of Disperse Orange 25 in the presence of 1-hydroxybenzotriazole.Â At an enzyme concentration of 0.45 EUmL-1 the peroxidase could successfully decolorize the dye up to a maximum of 61.2% with 0.2 mM 1-hydroxybenzotriazole. Maximum decolorization was recorded at a temperature of 40Â°C and at pH 4.0. The time for achieving maximum decolorization was 120min. Thus, the study suggests that T. diocia peroxidase could be a potential source for developing an inexpensive and efficient method for the treatment of recalcitrant Disperse Orange 25 dyes that are potentially toxic. Â Key words: Disperse Orange 25; 1-hydroxybenzotriazole; Decolorization; Trichosanthes diocia Peroxidase